Tema Utama Teologi Titus - Daniel Tumbel (Jurnal Teologi dan Pelayanan Kerusso, 2017)
The New Testament Epistle of Titus was written by Paul. He writes this letter to instruct Titus in regard to overseeing the believers in Crete. There are lots of things Titus must know and do to help these believers. The people in Crete are fairly new believers and they need to be organized into local churches. Titus’ responsibility is to appoint leadership in the churches and to ground the believers in sound doctrine. Spiritually qualified elders and doctrinally grounded believers will greatly promote spiritual unity in the local churches. The biblical teaching would provide the necessary components for biblical conflict resolution in the future. Paul writes Titus as his representative in Crete to aid the churches on a prophylactic way against Jewish false teachers by appointing those in leadership who are able tio manage God’s household well and stand against the false teachers, and by exhorting all believers to excel in good works so tha they might reach those outside of the church with the gospel.